High-Level Development of Multiserver Online Games. (15th July 2008) - Glinka, Frank; Ploss, Alexander; Gorlatch, Sergei; Müller-Iden, Jens
Abstract : Multiplayer online games with support for high user numbers must provide mechanisms to support an increasing amount of players by using additional resources. This paper provides a comprehensive analysis of the practically proven multiserver distribution mechanisms, zoning, instancing, and replication, and the tasks for the game developer implied by them. We propose a novel, high-level development approach which integrates the three distribution mechanisms seamlessly in today's online games. As a possible base for this high-level approach, we describe the real-time framework (RTF) middleware system which liberates the developer from low-level tasks and allows him to stay at high level of design abstraction. We explain how RTF supports the implementation of single-server online games and how RTF allows to incorporate the three multiserver distribution mechanisms during the development process. Finally, we describe briefly how RTF provides manageability and maintenance functionality for online games in a grid context with dynamic resource allocation scenarios.